2015
DOI: 10.3382/ps/pev092
|View full text |Cite
|
Sign up to set email alerts
|

Effect of yellow lupine (L. luteus) on the egg yolk fatty acid profile, the physicochemical and sensory properties of eggs, and laying hen performance

Abstract: The aim of this study was to evaluate the effects of different dietary inclusion of raw yellow lupine seed meal (YLM) on laying hen performance, the fatty acid (FA) profile, physicochemical, and sensory properties of eggs. A total of 224 Lohmann Brown laying hens at 32 wk age were fed isonitrogenous and isocaloric diets for 16 wk. The control diet contained soybean meal (SBM), and in study diets SBM was replaced with YLM at 100, 200, or 300 g/kg. In comparison with soybean, lupine seeds had a higher content of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

9
25
0
2

Year Published

2016
2016
2021
2021

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 25 publications
(36 citation statements)
references
References 20 publications
9
25
0
2
Order By: Relevance
“…In our study similar effect was observed at week 10 of the experiment. In contrast, Krawczyk et al (2015) did not confirm the negative effect of 30% yellow lupin seeds inclusion on laying performance, feed intake, FCR and egg weight. In this study, the feed intake amounted on average 126 g · d −1 · hen −1 and FCR -2.03 kg · kg −1 of egg weight.…”
Section: Discussionmentioning
confidence: 52%
See 2 more Smart Citations
“…In our study similar effect was observed at week 10 of the experiment. In contrast, Krawczyk et al (2015) did not confirm the negative effect of 30% yellow lupin seeds inclusion on laying performance, feed intake, FCR and egg weight. In this study, the feed intake amounted on average 126 g · d −1 · hen −1 and FCR -2.03 kg · kg −1 of egg weight.…”
Section: Discussionmentioning
confidence: 52%
“…In earlier investigations , similar effect was presented. Krawczyk et al (2015) recorded no differences in egg weight, shell thickness or strength after inclusion of 10-30% yellow lupin into laying hen diets.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…A linear increase (P ≤ 0.001) in the concentrations of polyunsaturated fatty acids was noted in meat from turkeys fed with lupin-based diets; this did not change the n-6/n-3 PUFA ratio, but improved the values of the atherogenic and thrombogenic indices (Krawczyk et al 2015). Zdunczyk et al (2014) study growth performance, gastrointestinal function and meat quality in growing-finishing turkeys fed diets with different levels (6, 12 and 18%) of yellow lupin (L. luteus) seeds meal (YLM).…”
Section: Production Efficiency Of Lupin In Poultrymentioning
confidence: 91%
“…Winkler et al [41] replaced corn and wheat in the diet of Hy-Line Brown hens with oats hulls, and they observed an increase in linoleic acid (C18:2n6c) levels and n6 fatty acids; however, no differences in oleic acid (C18:1n9c), palmitic acid (C16:0) and total PUFA were observed. However, Krawczyk et al [46] reported that the addition of yellow lupine to the bird diet resulted in a decrease of oleic acid (C18:1n9c) and consequently the MUFA content; but on the other hand, the PUFA content increased, as well as n6 content and the n6/n3 ratio. Recently, Secci et al [11] replaced soybean by black soldier fly meal in the Lohmann Brown Classic hen feed and observed changes in all fatty acids, except oleic acid (C18:1n9c).…”
Section: Effect Of Breed and Diet Type On Egg Fatty Acid Profile And mentioning
confidence: 99%